FSP1-positive fibroblasts are adipogenic niche and regulate adipose homeostasis - Zhang, Rui; Gao, Yuan; Zhao, Xiaotong; Gao, Mei; Wu, Yanjun; Han, Yingying; Qiao, Yuemei; Luo, Zheng; Yang, Li; Chen, Jianfeng; Ge, Gaoxiang (PLOS Biology, 2018)
Adipocyte progenitors reside in the stromal vascular fraction (SVF) of adipose tissues that are composed of fibroblasts, immune cells, and endothelial cells. It remains to be elucidated how the SVF regulates adipocyte progenitor fate determination and adipose homeostasis. Here, we report that fibroblast-specific protein-1 (FSP1)+ fibroblasts in the SVF are essential to adipose homeostasis. FSP1+ fibroblasts, devoid of adipogenic potential, are adjacent to the preadipocytes in the SVF. Ablation of FSP1+ fibroblasts in mice severely diminishes fat content of adipose depots. Activation of canonical Wnt signaling in the FSP1+ fibroblasts results in gradual loss of adipose tissues and resistance to diet-induced obesity. Alterations in the FSP1+ fibroblasts reduce platelet-derived growth factor (PDGF)-BB signaling and result in the loss of preadipocytes. Reduced PDGF-BB signaling, meanwhile, impairs the adipogenic differentiation capability of preadipocytes by regulating matrix metalloproteinase (MMP) expression, extracellular matrix remodeling, and the activation of Yes-associated protein (YAP) signaling. Thus, FSP1+ fibroblasts are an important niche essential to the maintenance of the preadipocyte pool and its adipogenic potential in adipose homeostasis.